2012
DOI: 10.1111/j.1537-2995.2012.03895.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma transfusion in liver transplantation: a randomized, double‐blind, multicenter clinical comparison of three virally secured plasmas

Abstract: Compared to both Q-FFP and S/D-FFP, use of MB-FFP was associated with a moderate increase in volume transfused, partly explained by a difference in unit volume and bleeding risk factors. Q-FFP was associated with fewer units transfused than either S/D-FFP or MB-FFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 32 publications
3
40
0
Order By: Relevance
“…Our results on 195 consecutive liver transplant recipients are in accord with previous observations 10,11 and suggest that SD-plasma administered as Octaplas is safe for patients undergoing liver transplantation. The relatively low concentrations of α2-antiplasmin and protein S in Octaplas, compared to products that have not undergone pathogen reduction, such as FFP, do not seem to have a major clinical impact.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results on 195 consecutive liver transplant recipients are in accord with previous observations 10,11 and suggest that SD-plasma administered as Octaplas is safe for patients undergoing liver transplantation. The relatively low concentrations of α2-antiplasmin and protein S in Octaplas, compared to products that have not undergone pathogen reduction, such as FFP, do not seem to have a major clinical impact.…”
Section: Discussionsupporting
confidence: 91%
“…One disadvantage of SD-plasma is that the SD-process inevitably reduces the levels of α2-antiplasmin and protein S, and could increase the risk of hyperfibrinolysis 8 or thromboembolic events such as pulmonary embolism during liver transplantation. 9 In addition to the track record of SD-plasma in Europe during the last two decades, both randomized controlled trials [10][11][12] and critical reviews 4,6 have suggested that these risks are largely theoretical. US SD-plasma was first introduced in 1998, but production was terminated in [2002][2003] in part due to thromboembolic complications not observed with European SD-plasma.…”
mentioning
confidence: 99%
“…The efficacy endpoints of the study were the volume of plasma, the number of RBC components, and the total dose of PLTs transfused during liver transplant and the 7 days after surgery. The volume of plasma transfused provides an integrated clinical endpoint indicative of hemostasis reflecting the clinical decision to transfuse plasma either for active bleeding or for coagulopathy associated with risk of bleeding . In the setting of the coagulopathy of liver disease, and especially during transplant, correction of abnormal clinical laboratory tests of hemostasis (prothrombin time or activated partial thromboplastin time) are not highly correlated with clinical hemostasis and frequently do not correct substantially after plasma transfusion …”
Section: Methodsmentioning
confidence: 99%
“…In some countries, plasma prepared with pathogen inactivation (PI) has been implemented to reduce the risk of TTI . As different PI methods are introduced into routine clinical practice, it is relevant to assess the impact of these interventions on therapeutic efficacy and safety .…”
mentioning
confidence: 99%
“…), was also not altered by the treatment. TEG‐R, PT, and APTT, acting as surrogates for plasma protein function, did not change. WBCs, total protein, albumin, globulin, troponin, and fibrinogen did not differ in either group.…”
Section: Discussionmentioning
confidence: 91%